PENGARUH PENGGUNAAN KONTRASEPSI SUNTIK TERHADAP SEKSUALITAS AKSEPTOR DI RSIA MASYITA MAKASSAR - Dahniar; Firawati (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2021)
Injectable contraception is a way to prevent pregnancy by giving hormones that are given intramuscularly in the gluteus region, namely the buttocks area. Birth control injections containing DMPA further increase the risk of experiencing sexual dysfunction. With the increasing number of injection family planning participants, it is necessary to conduct research on this issue. This study aims to determine the effect of using injectable contraceptives on acceptors at RSIA Masyita Makassar, the magnitude of the risk faced by DMPA injection respondents compared to those who used 1 month, and users of old and new contraceptives. This type of research uses purposive sampling technique and a sample of 35 respondents. The instrument used is a questionnaire sheet with a cross sectional approach. Data analysis was performed by univariate analysis with frequency distribution and bivariate with chi-square test with a significance level of p < 0.000. The results showed that 28 people experienced sexual dysfunction or sexual disorders where there were 24 old users (68.6%) and 4 new users (11.4%). The results of the analysis showed that the age of the injection acceptor was associated with sexual dysfunction in women at RSIA Masyita Makassar.